PERBANDINGAN TEKNIK PEMERIKSAAN CARPAL CANAL PROYEKSI TANGENSIAL METODE GAYNORT-HART INFEROSUPERIOR DAN CARPAL CANAL SUPEROINFERIOR UNTUK MENDAPATKAN GAMBARAN OS PSIFORM: Comparison of Tangential Projection Carpal Canal Examination Techniques using Gaynort-Hart Inferosuperior and Carpal Canal Superoinferior Methods to Obtain Psiform OS Images - Santa - Mareta (JURNAL TERAS KESEHATAN, 2021)
Carpal Canal is a basin created by Palmar from Metacarpal. One of several revenue projections made, one of which is the carpal canal. The tangential method is the inferosuperior gaynor-hart method and the superoinferior carpal canal. This research is to learn which method is better to see Os Psiform. The study was conducted at the Radiology Unit of Aisyiyah Public Hospital Padang in September 2019. The method used was quantitative with experimental studies, the results of this radiograph were read out by five respondents, data were processed using the Mean Score and Statistical Product Service Solution (SPSS) formula with the Wilcoxon Test. The results of the study for the description of Os Psiform free of superposition the average value in the inferosuperior method was 3.56 and in the superoinferior method was 2.64. While using SPSS obtained with a significant value of 0.039 (p value <0.05) then H0 is rejected and Ha is accepted, which means there are significant differences from the two methods.